Candida albicans Osteomyelitis Pubis: The Possible Pathogenic Role of Pelvic Irradiation. (3rd December 2017) - Iacuzzo, Cristiana; Monticelli, Jacopo
Abstract : Radiation to the pelvis, mainly directed against either prostatic or gynecologic cancers, is burdened by a lot of complications. The genitourinary tract is most frequently involved, presenting with bladder irritation, incontinence, and fertility disorders. However, side effects of radiation can also affect the bone, usually causing an osteolytic process which deteriorates the bone structure and leads to fractures, avascular necrosis, and other pathological insults. Here, we describe a case of Candida albicans osteomyelitis of the pubic symphysis as late complication of pelvic radiotherapy performed against prostate cancer.